Fraction fun - Adler, David A.; Tobin, Nancy (New York : Holiday House, 1996)
A basic introduction to the concept of fractions.
Wilson's Children
Elem. School Library Collection
School Library Journal
4.2
K-3
Keywords: Fractions -- Juvenile literature; Fractions; Fractions